2014
DOI: 10.1071/sh14015
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against oncogenic human papillomavirus infection in HIV-infected populations: review of current status and future perspectives

Abstract: Abstract. Background: Men and women with HIV infection are at increased risk of developing cancers associated with human papillomavirus (HPV). The two licensed prophylactic HPV vaccines protect against de novo infection with HPV-16 and HPV-18, which cause the majority of HPV-associated cancers. Currently, no vaccine efficacy data are available for persons with HIV infection. Nevertheless, some countries have implemented specific HPV vaccination recommendations for HIV-positive populations. To specifically reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…In this study, it was also found that HPV18 was higher and HPV45 lower in HIV endemic areas. However, the significance of this finding remains to be understood in light of emerging evidence that HPV vaccines are immunogenic even in HIV infected individuals despite need for more long term data [41]. Further, Ndiaye et al highlighted the importance of HPV-45 as an important candidate for future vaccines, despite the fact that varying degrees of cross protection against HPV45 have been described for the current bivalent and quadrivalent vaccines [38].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was also found that HPV18 was higher and HPV45 lower in HIV endemic areas. However, the significance of this finding remains to be understood in light of emerging evidence that HPV vaccines are immunogenic even in HIV infected individuals despite need for more long term data [41]. Further, Ndiaye et al highlighted the importance of HPV-45 as an important candidate for future vaccines, despite the fact that varying degrees of cross protection against HPV45 have been described for the current bivalent and quadrivalent vaccines [38].…”
Section: Discussionmentioning
confidence: 99%
“…Vaccinations are recommended for girls and women aged 9 years up to 25 years old prior to HPV exposure [29]. There are few studies investigating the immunogenicity and safety of the HPV-vaccination in HIV-infected populations [30]. However, from the available evidence, both the bi- and quadrivalent HPV-vaccines have demonstrated high seroconversion rates and acceptable safety profiles in various HIV-infected populations (children, female adolescents and adults).…”
Section: Hpv-vaccination For the Primary Prevention Of Invasive Cervimentioning
confidence: 99%
“…Antibody titres were 50% and 70% lower at 7 and 12 months in the HIV-infected group compared to the HIV-uninfected group [30,34]. However, HPV-16 and HPV-18 geometric mean titres in the HIV-infected group remained 26- and 16-fold higher at one year than those reported in healthy women (15–25 years) who cleared a natural infection.…”
Section: Hpv-vaccination For the Primary Prevention Of Invasive Cervimentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 HPV vaccine trials among HIV-infected young women and men demonstrated that HPV type-specific immune responses to vaccination are generally robust. 1016 However, studies have demonstrated substantially lower seropositivity rates for HPV18 compared to HPV6, 11, and 16. In one study, 32.4% of those not on antiretroviral therapy (ART) and 13.3% of those on ART became (or remained) seronegative for HPV18 at 48 weeks after vaccination.…”
Section: Introductionmentioning
confidence: 99%